Environmental Awareness Message in the Posts of the Instagram Account 'Systogreen.id' (A Study of Roland Barthes' Semiotic Analysis) - Fitriani, Annisya (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Social media is an online platform used for interaction, information sharing, and promoting businesses or personal branding. Instagram, as one of the photo and video-based social media platforms, is used to share visual content, interact with other users, and promote products, services, or personal branding. One Instagram account that focuses on environmental issues is @systogreen.id, which conveys messages and education about environmental awareness through its posts. Each post contains both verbal and non-verbal messages that can be analyzed to understand the underlying meanings and how these messages encourage environmental awareness in society. This study aims to describe the messages, both explicit and implicit, contained in the Instagram posts of @systogreen.id. The research method used is qualitative, with an approach based on Roland Barthes' semiotic theory and environmental theory. The results of the study show that the Instagram posts of @systogreen.id convey a variety of messages related to waste separation, organic waste management, as well as education and environmental awareness. These messages are effectively packaged through visuals and text, capable of inspiring society to be more environmentally conscious.